POTENSI PRODUKSI BEBERAPA VARIETAS UNGGUL BARU TANAMAN PADI (Oryza sativa L.) PADA KELAS BENIH POKOK DI KECAMATAN BANJAR KABUPATEN PANDEGLANG - AM, Kartina (Jurnal Agroekoteknologi, 2011)
The research was aimed to know production potency of five New Superior Varieties of Rice Plant (Oryza sativa) of Stock Seed that was grown in Banjar District Pandeglang Regency of Banten Province. Research was conducted in the village of Kadu Bale, Banjar District Pandeglang Regency in May until August 2011. The research used a Randomized Completely Block Design with five new superior varieties as factor that consisted of five levels with five replications. Parameter observed were: 1) the percentage of replace with new rice seedling, 2) the number of maximum tillers, 3) the percentage of non productive tiller, 4) age of panicle appear, 5) number of panicle, 6) the percentage of green panicle more than 80 % , 7) number of grain each longest panicle, 8) percentage of empty grain each panicle, 9) weight of 100 full grain, 10) ratio of long and weight full grain, 11) production of dry harvest grain , and 12) productivity of dry harvest grain per hectare. The result showed that qualitative observed of the six varieties still suitable with the their description. The quantitative observed was influenced by physical condition naturally and cultivation. For positive effect were showed by the parameter observed : 1) the percentage of replace with new rice seedling, 2) the number of maximum tillers, 3) number of panicle, 4) weight of 100 full grain, but for negative effect were showed by the parameter observed: 1) the percentage of green panicle, more than 80 % , 2) number of grain each longest panicle, 3) percentage of empty grain each panicle, and 4) production of dry harvest grain. For cultivation action gave the best physiology effect only to Ciherang. The percentage of green panicle more than 80 % was 6,39 % fewer than another varieties (inpari 1, Inpari 7, Inpari 8, and Inpari 13).Key words: rice, stock seed, new superior varieties, potential production.